The inflammatory markers combined with CA125 may predict postoperative survival in endometrial cancer - Hongxing Lin; Wenhui Zhong; Liying Zhong; Chengwen Que; Xiaosong Lin (Journal of Obstetrics and Gynaecology)
Background Endometrial cancer (EC) has a high latency, making prognosis difficult to predict. Cancer antigen 125 (CA125) is not specific as a tumour marker for EC; however, complete blood count (CBC) inflammatory markers are associated with prognosis in various malignancies. Thus, this study investigated the value of CBC inflammatory markers combined with CA125 levels in predicting the prognosis of patients with EC.Methods In this study, 517 patients with EC were recruited between January 2015 and January 2022, and clinical characteristics, CBC inflammatory markers, and CA125 levels were assessed. Differences in each index at different EC stages and the correlation between the index and EC stage were analysed, and the influence of the index on EC prognosis was evaluated.Results Platelet distribution width (PDW) levels were significantly lower in patients with advanced EC than in those with early EC, whereas the systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and CA125 levels were significantly higher in patients with advanced EC (all P < 0.05). ROC curve and multivariate logistic regression analyses indicated that decreased PDW and increased CA125 levels were independent risk factors for EC staging progression. In addition, multivariate Cox regression analysis showed that the combination of low PDW and high CA125 (PDW + CA125 = 2) was an independent prognostic factor of survival in EC patients. Kaplan-Meier survival analysis indicated that patients with low PDW and high CA125 had worse overall survival.Conclusions The PDW and CA125 score may be an independent prognostic factor for postoperative overall survival in patients with EC and a useful marker for predicting the prognosis of these patients.